The development of supporting the elite athletes in the UK: From athlete and career education program to performance lifestyle - Lee, P.; Jiang, R. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
This discussion is about elite, or high performance, sport and primarily about how the UK provides life support for the elite athletes with a concern of major contributions of implementing ACE UK program in the 1999-2004 period and later the Performance Lifestyle program since 2004. Methods: The documentary-based element takes the form of qualitative content analysis, which applied to the form of analysis of a number of British sport official reports, academic articles, and media commentaries. In total, 107 references were reviewed and 53 commentaries were identified to conduct this research. The data was subject to analysis and coding employing the NVivo 9 software package. Results: In 1999 UK Sport, as the government agency with a remit for elite sport, administers an Athlete and Career Education (ACE UK) program based on a similar scheme that has been in place in Australia. ACE UK was set up to provide athletes with the skills to cope with the special demands of higher-level sport and to help them prepare for life after sport (UK Sport, 2001). Five major services were provided through the ACE UK program, namely, Personal Development Courses, Education Guidance, Career Planning, Olympic and Paralympic Employment Network (OPEN) (North & Lavallee, 2004). Since its inception in 1999, the ACE UK program has had a relatively high level of usage amongst the elite UK athlete population (UK Sport, 2001). In 2004, the ACE UK program has been replaced with the Performance Lifestyle program which covers the following three main areas: Lifestyle support, Careers and Employment Advice, and Education Guidance. Since 2009 the Performance Lifestyle service has been delivered through the English Institute of Sport. Discussion: The above programs of lifestyle support and preparation for life after sport contain all or some of the following elements: career advice; educational support, along with personal finance; and media and presentation skills training (Green & Oakley, 2001, 262). This implies that Performance Lifestyle is a program designed to help athletes balance all other aspects of their life with their sport. And, the major contributions of the Performance Lifestyle are concluded as the followings: contributions to medals, athlete welfare, athlete focus, self-efficacy balance, and maybe transferable to other domains.